Strengthening Student Character Through Tapak Suci Extracurricular Activities - Ikhwan, Afiful; Anjelita, Rona; Kartiko, Ari; Zukhrufin, Fina Kholij; Ikhwan, Aisyah Nuril (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Character education plays an important role in education, aiming to teach honesty, discipline, creativity, responsibility, hard work, and religiosity in early daily life through habituation and role models. Implementing character education through formal, informal and non-formal education is very important to foster positive personalities in students and combat the prevalent moral crisis in society. This study focuses on strengthening the religious character of students through tapak suci extracurricular activities at SMA Muhammadiyah 1 Ponorogo. This study aims to identify the religious characteristics of tapak suci activities that support the strengthening of student character, the process of strengthening religious character that is carried out, and the impact of tapak suci activities on students. This study uses a qualitative field method that is descriptive and non-statistical with a phenomenological approach; data is collected through triangulation techniques that include direct observation, in-depth interviews with various sources, and documentation; data analysis is carried out inductively, with steps of data reduction, data presentation, and verification. The study results showed that tapak suci activities instilled the character values ​​of responsibility, good manners, discipline, faith, piety, honesty, and leadership. The character-strengthening process was carried out through a holistic training program, a personal approach, routine training combined with religious values ​​such as mutual respect, patience, obedience to regulations, obedience to worship, prayer, participating in studies and organizational activities and periodic evaluations. The positive impact of this activity can be seen in the increase in obedience to worship, strengthening of moral values, development of Islamic character, and increased academic and non-academic achievements of students. This study confirms that tapak suci activities effectively build students' strong religious and moral character, preparing them to become individuals with high integrity and positively contribute to society.